CHANGES IN RESTING POTENTIAL AND ION ABSORPTION INDUCED BY LIGHT IN A SINGLE PLANT CELL - NAGAI, REIKO; TAZAWA, MASASHI (Oxford University Press, 1962)
<l type="ord"> Effect of light on ion absorption and resting potential of the internodal cell of Nitella flexilis was investigated under various conditions. On illumination, the resting potential increased by about 30 m V in 10−4 M KCl and by about 60 m V in 10−4 M NaCl solution. A similar photoelectric response was also observed in 10−3 M KCl, 10−2 M CaCl 2 and 5 × 10−2 M CaCl 2 solutions, but not at all in 10−2 M KCl solution. Absorption of ions by the cell took place in parallel with the light-induced change in resting potential. Red and blue lights were very effective in increasing the resting potential, while green light was almost ineffective. These different effects of color lights were in good agreement with their effects in increasing the osmotic value of the cell. The photoelectric response was not affected by phenylurethane, which, on the other hand, strongly inhibited the light-induced ion absorption. The uptake of ions by the cell from the external medium into the vacuole is assumed to proceed in two different steps: the first is the process involving the ion movements across the outermost plasmalemma, and the second is that involved in the transport of ions through the cytoplasmic layer and tonoplast. The former process is considered to be influenced by the increase in resting potential probably caused by the light absorbed by chlorophyll. The process was, however, suggested to be independent of photosynthesis. On the other hand, the latter process is supposed to be related to photosynthesis. A discussion was made along this line. </l>